Contracts in trade and transition : the resurgence of barter - Marin, Dalia (MIT Press, 2002)
An institutional approach to explaining countertrade and barter in international trade and domestic trade in transition economies. Difficulties in contract enforcement impede international transactions in the world economy and domestic transactions in transition economies. In Contracts in Trade and Transition, Dalia Marin and Monika Schnitzer explain how barter as an economic institution can facilitate contract enforcement across national borders in international trade and within borders in transition countries. The authors show that international countertrade--tying an export to an import--emerged in the 1980s in response to the international debt crisis when Western creditors refused to finance imports to developing countries and Eastern Europe. Barter--the exchange of goods without the use of money--reemerged in transition economies in the 1990s in response to a domestic debt crisis when banks in transition countries were reluctant to provide finance to firms. Countertrade and barter introduce a deal-specific form of collateral that addresses the lack of creditworthiness of countries and firms. Drawing on contract theory, the authors argue that parties might want to pay in goods rather than cash or link an export with an import as in countertrade to solve incentive problems that otherwise would prevent any trade from taking place. The incentive problems they discuss are the technology transfer problem to developing countries and the "lack of trust" problem in the former Soviet Union